PERsistent Sitagliptin treatment & Outcomes (PERS&O 2.0) study, long-term results: a real-world observation on DPP4-inhibitor effectiveness - Antonio Carlo Bossi; Valentina De Mori; Carlotta Galeone; Davide Pietro Bertola; Margherita Gaiti; Annalisa Balini; Denise Berzi; Franco Forloni; Giancarla Meregalli; Federica Turati (BMJ Open Diabetes Research & Care, 2020)
Introduction Sitagliptin is a dipeptidyl peptidase 4 inhibitor for the treatment of type 2 diabetes (T2D). Limited real-world data on its effectiveness and safety are available from an Italian population.Research design and methods We evaluated long-term clinical data from the single-arm PERsistent Sitagliptin Treatment & Outcomes (PERS&O) study, which collected information on 440 patients with TD2 (275 men, 165 women; mean age 64.1 years; disease median duration: 12 years) treated with sitagliptin ‘add-on’. For each patient, we estimated the 10-year cardiovascular (CV) risk using the UK Prospective Diabetes Study (UKPDS) Risk Engine (RE). Drug survival was evaluated using Kaplan-Meier survival curves; repeated measures mixed effects models were used to evaluate the evolution of glycated hemoglobin (HbA1c) and CV risk during sitagliptin treatment.Results At baseline, most patients were overweight or obese (median body mass index (BMI) (kg/m2) 30.2); median HbA1c was 8.4%; median fasting plasma glucose: 172 mg/dL; median UKPDS RE score: 24.8%, being higher in men (median 30.2%) than in women (median 17.0%) as expected. Median follow-up from starting sitagliptin treatment was 5.6 years. From Kaplan-Meier curves, the estimated median drug survival was 32.8 months when considering discontinuation for any cause and 58.4 months when considering discontinuation for loss of efficacy. A significant improvement in HbA1c was evident during treatment with sitagliptin (p<0.01): the reduction was rapid (median HbA1c after 4–6 months: 7.5%) and continued at longer follow-up. When comparing patients treated with sitagliptin versus those stopping sitagliptin and switching to another antihyperglycemic drug, we detected a significant difference in the evolution of HbA1c in favor of patients who continued sitagliptin treatment. The UKPDS RE score at 10 years and the BMI significantly improved during treatment with sitagliptin (p<0.001). Adverse events were relatively uncommon.Conclusion Patients with T2D treated with sitagliptin achieved an improvement in metabolic control and a reduction in CV risk and did not experience relevant adverse events.